2022
DOI: 10.3390/life12101543
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of the Upper-Airway Adipose Tissue in the Pathogenesis of Obstructive Sleep Apnoea

Abstract: This study aimed to analyse the thickness of the adipose tissue (AT) around the upper airways with anthropometric parameters in the prediction and pathogenesis of OSA and obstruction of the upper airways using artificial intelligence. One hundred patients were enrolled in this prospective investigation, who were divided into control (non-OSA) and mild, moderately severe, and severe OSA according to polysomnography. All participants underwent drug-induced sleep endoscopy, anthropometric measurements, and neck M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…This study corroborates the association between an increased risk of NC enlargement and OSAS, thereby aligning with the research conducted by Altan Onat et al and Viktória Molnár et al 15,18 Altan Onat et al undertook a comprehensive observational study involving 25 patients with severe OSAS (Apnea-Hypopnea Index [AHI] ≥ 30 events per hour) and 19 with non-severe OSAS (AHI < 30 events per hour). Their findings indicated a positive correlation between increased NC and the severity of OSAS.…”
Section: Osas and Neck Circumferencesupporting
confidence: 89%
See 1 more Smart Citation
“…This study corroborates the association between an increased risk of NC enlargement and OSAS, thereby aligning with the research conducted by Altan Onat et al and Viktória Molnár et al 15,18 Altan Onat et al undertook a comprehensive observational study involving 25 patients with severe OSAS (Apnea-Hypopnea Index [AHI] ≥ 30 events per hour) and 19 with non-severe OSAS (AHI < 30 events per hour). Their findings indicated a positive correlation between increased NC and the severity of OSAS.…”
Section: Osas and Neck Circumferencesupporting
confidence: 89%
“…15 Similarly, Viktória Molnár et al conducted an analysis utilizing magnetic resonance imaging (MRI) to examine the adipose tissue parameters of the upper airways in 36 non-OSA control subjects, 32 patients with mild OSAS, and 32 with moderately-severe OSAS. 18 By applying artificial intelligence techniques to these MRI data, they identified age, percentage of tongue fat, and NC as crucial predictors of OSAS. Their results demonstrated that an increase in NC was positively correlated with OSAS severity and served as an independent predictor of severe OSAS.…”
Section: Osas and Neck Circumferencementioning
confidence: 99%
“…Their investigation found that anthropometric measurements and MRI AT values both reliably predicted OSA; the most significant predictive criteria were body mass index, age, neck circumference, tongue midline, and parapharyngeal fat levels. 27 The above studies demonstrate how most contemporary studies on children’s OSA have extensively depended on statistical analysis of clinical examination or questionnaire data, regardless of the data or research methodology used. Due to the paucity of available data on OSA, it is difficult to accurately determine the severity of the disease and accurately depict the patient’s true clinical state.…”
Section: Introductionmentioning
confidence: 95%
“…A number of groups have demonstrated the use of the ML-based analysis of MRI to automatically segment upper-airway structures, including the pharynx, tongue, and soft palate, that may facilitate large-scale epidemiological analyses in OSA patients in the future [ 80 , 81 , 82 ]. Molnar et al [ 83 ] used an AI analysis based on pharyngeal adipose tissue thickness derived from MRI, sex, and neck and waist circumference to separate patients with airway obstruction from those without. In a novel approach to airway measures, ML-supported computational fluid dynamics analysis has been used to predict OSA-related airflows [ 84 ].…”
Section: Applying Machine Learning and Artificial Intelligence To Obs...mentioning
confidence: 99%